Fish active packaging with ZnO/Fe-MMT nanoparticles - Kaveh Rahmanifarah; Mehdi Mahmoudian; Somayeh Mahmoudi Eskandarabadi (Scientific Reports)
Abstract Today, active packaging has become essential to increase food safety and decrease food spoilage. In this study, the aim was to delay spoilage and increase the shelf life of rainbow fish fillets with a new hybrid nanocomposite active packaging. Packaging was fabricated with Ethylene vinyl acetate and active compounds such as rosemary extract, zinc oxide nanoparticles, and modified iron (Fe-MMT). Various experiments such as XRD and FESEM analyses were performed on active films, and for fish fillets, total sulfhydryl, volatile nitrogen, and lipid oxidation tests were conducted to determine the shelf life of fish fillets in packages. The highest recorded increase in volatile nitrogen, which indicates spoilage in fish fillets, was 9.45 mg 100 g−1, well below the spoilage limit of 25 mg 100 g−1. It can be concluded that the implementation of this new hybrid nanocomposite active packaging not only enhances the shelf life of rainbow fish fillets by effectively delaying spoilage but also maintains their sensory qualities. These findings suggest that such active packaging solutions could be widely adopted in the seafood industry to improve food safety, reduce waste, and provide consumers with fresher products.